2016
DOI: 10.1016/j.burns.2015.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole-body vibration exercise on bone mineral content and density in thermally injured children

Abstract: Background Loss of bone mass, muscle mass, and strength leads to significant disability in severely burned children. We assessed the effects of exercise combined with whole-body vibration (WBV) on bone mass, lean mass (LM), and muscle strength in children recovering from burns. Methods Nineteen burned children (≥30% total body surface area [TBSA] burns) were randomly assigned to a 6-week exercise regimen either alone (EX; n = 10) or in combination with a 6-week WBV training regimen (EX+WBV; n = 9). WBV was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…There were only 2 trials including 43 children and adolescents to assess the influence of WBV on muscle mass or lean mass. [ 22 , 27 ] Study participants included boys and girls aged 12 to 18 years with Down syndrome [ 27 ] and thermally injured children. [ 22 ] The results indicated that there were no significant differences of lean mass or muscle mass between experimental and control groups (SMD = −0.31, 95%CI: −2.51, 1.89; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There were only 2 trials including 43 children and adolescents to assess the influence of WBV on muscle mass or lean mass. [ 22 , 27 ] Study participants included boys and girls aged 12 to 18 years with Down syndrome [ 27 ] and thermally injured children. [ 22 ] The results indicated that there were no significant differences of lean mass or muscle mass between experimental and control groups (SMD = −0.31, 95%CI: −2.51, 1.89; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of consideration, a plausible approach may be to use a combination of strategies including exercise and whole-body vibration therapy. This combination has been successfully used in youth with severe burns [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effect of WBV training, in terms of increased BMD and quadriceps strength, was also demonstrated in a study on patients with hemophilia [35]. WBV training has also been studied in children recovering from burns who performed regular exercise in conjunction with WBV, which improved leg strength but with reportedly small decreases in some BMC and BMD measurements [36]. Leonard et al [37] conducted a large WBV intervention in a pediatric cohort of Crohn's disease and found increased vertebral trabecular BMD, but inconsistent effects on axial and appendicular trabecular volumetric BMD.…”
Section: Effect Of Wbv Intervention In Other Groupsmentioning
confidence: 95%